Genetic evaluation of sire for milk production and its composition traits in Murrah buffaloes - chitra, anil (Indian Journal of Dairy Science, 2016)
First lactation milk production and its constituent’s records of 315 Murrah buffaloes sired by 47 bulls and having 3 or more daughters were used to evaluate sires for first lactation 305 milk yield (FLMY305), 305 fat yield (FLFY305), 305 solid not fat yield (FLSNF305) and 305 total solid yield (FLTS305) traits. The objective of the study was to estimate the sire breeding value and to compare various methods of sire evaluation viz., least squares (LS), best linear unbiased prediction (BLUP) and simple regressed least squares technique (SRLS) in terms of accuracy and efficiency. Heritability estimates by paternal half-sib correlation method were 0.30±0.18, 0.29±0.08, 0.30±0.18 and 0.30±0.18 for FLMY305, FLFY305, FLSNF305 and FLTS305, respectively. The methods were compared on the basis of error variance, coefficient of determination and rank correlations among the methods. Error variance was observed to be minimum under BLUP method for all the traits considered (FLMY305, FLFY305, FLSNF305 and FLTS305). Therefore, this method was taken as the most efficient one. It was concluded based on all the criteria to compare the effectiveness of different methods that BLUP method was more efficient and accurate compared to other methods owing to lowest error variance and highest R2-value.